Penubuhan mimer dalam proses kreatif pertunjukan pantomim - Dwi Febrianto (Masyarakat, Kebudayaan dan Politik, 2015)
Pantomime is a show that relies to actor's body movement and facial expression. The question proposed in this research is how the mime actor's creative process related to body movement's usage in a pantomime show? Researcher conducted the research by phenomenological approach. Targeted informants are 1) Theater community Sendratasik coach and Lecturer form UNESA; 2) Head of Sendratasik theater UNESA; 3) Show's director; 4) mime actors; 5) active member of Sendratasik theater. This research concludes that in order to reach total appreciation to the role, a mime actor practiced various activites long before the performance day. These activites include joint practice or personal appreciation beyond the practice time. Mime actor's personal experience is an important thing for actor to play the role. Religious experiences also influence training session or mime actor's effort in understanding the role. This is suitable with embodiement function which performed personally or communally by mime actor(s).